1998
DOI: 10.1046/j.1365-2648.1998.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

The participants’ views of childbirth education: is there congruency with an enablement framework for patient education?

Abstract: Although nursing research literature in the area of patient education is rich in number, methodologies used have limited generalizability and cohesiveness. Previous theoretical work has suggested an enablement framework for patient education across content areas. This study approaches patient education from the participant's view and engages the recipients in describing their goals for the process. Seven primiparous women taking childbirth education were asked about their reasons/goals for attending, anticipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
6
31
0
Order By: Relevance
“…This finding confirms results from other studies on childbirth education showing that parental education exclusively prepares for normal birth (Cliff & Deery, 1997;Stamler, 1998). Midwives in Sweden are responsible for normal birth, often in complex clinical settings.…”
Section: Discussionsupporting
confidence: 82%
“…This finding confirms results from other studies on childbirth education showing that parental education exclusively prepares for normal birth (Cliff & Deery, 1997;Stamler, 1998). Midwives in Sweden are responsible for normal birth, often in complex clinical settings.…”
Section: Discussionsupporting
confidence: 82%
“…They found that, through the classes, they not only gained the knowledge they had desired but also gained other benefits. Consistent with Stamler's (1998) findings, the women described how the classes had strengthened their relationships with their husbands, increased their confidence in themselves, and empowered them to have some control over a situation that was often out of their control.…”
Section: Implications For Practicesupporting
confidence: 63%
“…All of the participants were married, Caucasian, spoke English, and had completed at least some college. Although homogeneous, the sample was characteristic of the childbirth education attendees reported in the literature (Koehn, 2002;Nichols & Gennaro, 2000;Sims-Jones et al, 1998;Spiby et al, 2003;Stamler, 1998) and in the researcher's setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mainly focused on evaluating institutional education programs using a cognitive and motivational approach (Knowles, 1980;Rasmussen, 1989;Redman, 1993), utilizing primarily quantitative analyses that deal with conceptual variables like patient's knowledge and compliance. In the area of obstetrics and gynecology (OBGYN), research has dealt with teaching patients childbirth and child-rearing techniques (Stamler, 1997), in which patient education is recognized as a key element for providing quality medical care (Redman, 1993;Tilly, 1987). Research on patient-centered medicine suggests individually tailored teaching styles allow patients to administer self-care more effectively (Redman, 1993).…”
Section: Introductionmentioning
confidence: 99%